Evaluation Medicine Availability Before and After NHI Implementation at Health Centers in Keerom District, Papua Province - Ivonie Carolien; Achmad Fudholi; Dwi Endarti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The availability of medicine in health center is associated with medicine management system and should be supported by adequate and sustainable resource. The Implementation of National Health Insurance (NHI) program will increase the need for medicine, to describe the medicine availability at primary health center before and after NHI, to identify the factors affect the availability, to compile solutions to increase the medicine availability at health centers in Keerom District. This research method was a descriptive. The data has been gathered based on observations to primary health center’s document of 2012 to 2015, for 35 indicator medicine, and interview with  the medicine manager and  the chief of health center, the manager of pharmacy district and the chief of health office at Keerom District. The data analysis was presented by charts, tables, and in narrative description. The results were  the availability of medicine at the health centers in Keerom District, before and after NHI program was same, by category of supply was safe, but insufficient as health center’s need. The medicine availability was not appropriate with essential medicine list and illness, the expired and defected medicine still be found, and  stock out time increased after NHI. In that period, the factors affect were, the demand process has not been optimal, insuffiecient and uneven distribution, lack of personel and  inadequate supporting for drug distribution charges the solution proposed were,  to improve knowledge and skill for medicine manager of health center, to plan pharmacist requirements, to set up medicine management information system, to do the integrated medicine planning and to provide the enough cost of distribution.